The Impact of Reconciliation on the Termination of Criminal Proceedings: A Comparative Study with the Reconciliation of Imam Al-Hasan (peace be upon him) - Sabah Mohsen Jaloud Al-Jadri, Asst. Lect (lark, 2025)
Every reconciliation arises from specific circumstances and must yield outcomes that benefit those involved, whether righteous or not, even if they are initially unaware of its true purpose. In time, the value becomes evident. The reconciliation of Imam Al-Hasan (peace be upon him) with Muawiyah ibn Abi Sufyan was driven by compelling reasons, yet it ultimately brought about welfare and reform for the Islamic nation, and safeguarded Islamic principles from the treachery of the wicked and the betrayal of the deceitful. When Imam Al-Hasan (peace be upon him) assumed leadership of the Muslim nation following the martyrdom of his father, Amir al-Mu’minin (peace be upon him), the community was overwhelmed by turmoil and sedition. The Umayyads, in their quest for power and legitimacy, contributed greatly to this unrest. At a time when many Muslims were unaware of the deviation inherent in the Umayyad approach to religious teachings, tensions escalated to a breaking point. Imam Al-Hasan prepared an army to confront the Umayyad forces, and the drums of war began to sound. However, widespread Umayyad propaganda falsely claimed that Imam Al-Hasan had already reconciled with Muawiyah. After several assassination attempts against him, the Imam found himself compelled to conclude a peace treaty with Muawiyah.
Keywords: reconciliation, criminal mediation, waiver, complaint, alternative dispute resolution.